Preparation method of tannic acid-based papermaking additive

Through the synergistic action of tannin acid and cationic starch and the combination of alkylkane dimers, a composite gum solution was prepared, which solved the problem of poor applicability of existing papermaking additives under acidic conditions, and achieved the improvement of multiple properties of paper.

CN119571664APending Publication Date: 2025-03-07NORTHEAST FORESTRY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411876287.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing papermaking additives have poor applicability under acidic conditions, making it difficult to take into account the antioxidant, antibacterial, hydrophobic and mechanical properties of paper.

Method used

The synergistic effect of tannin acid and cationic starch is used to combine alkylkone dimers to prepare composite applicator solution, and coated paper is prepared through impregnation, pressing and drying processes.

Benefits of technology

It significantly improves the antioxidant, antibacterial, hydrophobic and mechanical properties of paper, and meets the needs of high-end food packaging paper and medical paper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571664A_ABST
    Figure CN119571664A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of papermaking additives, and discloses a preparation method of a tannic acid-based papermaking additive, which comprises the following steps: 1) preparation of a tannic acid solution: dissolving tannic acid in deionized water, and stirring to form a uniform solution; 2) preparing a cationic starch solution: dissolving cationic starch in deionized water, heating and stirring until the solution is uniform; and 3) preparing a tannic acid-cationic starch emulsion: slowly dropwise adding the cationic starch solution into the tannic acid solution, heating to a set temperature, keeping the reaction, and cooling to obtain the tannic acid-cationic starch emulsion. The tensile strength and anti-cracking strength of paper are remarkably improved through modified tannic acid, the fiber dispersity and the sizing liquid retention rate are improved, the problem that a traditional auxiliary is insufficient in performance is solved, meanwhile, an environment-friendly modification technology is adopted, use of toxic chemical reagents is reduced, the long-term stability and environment friendliness of the auxiliary are improved, and the requirement for sustainable development is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of papermaking additives, in particular to a method for preparing a tannic acid-based papermaking additive. Background Art

[0002] At present, the papermaking industry widely uses sizing agents to improve the mechanical properties, moisture resistance and surface smoothness of paper. Commonly used sizing agents include neutral sizing agents (such as alkyl ketene dimer, AKD) and acidic sizing agents (such as rosin emulsion). Among them, AKD has become a commonly used neutral sizing agent in modern papermaking due to its excellent hydrophobic properties and stability in neutral and alkaline environments. However, the performance of AKD decreases under acidic conditions, and its application in non-wood fiber papers such as bamboo pulp paper is limited. At the same time, with the increasing demand for functional papers such as food packaging paper and medical paper, the market has put forward higher requirements for the antioxidant, antibacterial and comprehensive performance of paper. A single traditional sizing agent can no longer meet the diverse needs.

[0003] Traditional sizing processes mostly rely on synthetic chemical additives. Although they can improve the hydrophobicity and mechanical properties of paper to a certain extent, it is difficult to take into account special functions such as antioxidant and antibacterial properties. At the same time, these synthetic additives are often not environmentally friendly enough, which restricts the development of green manufacturing. For example, although AKD has excellent hydrophobic properties, it is easily hydrolyzed and ineffective under acidic conditions; although rosin emulsion is suitable for acidic papermaking processes, its sizing effect is poor and it is difficult to significantly improve the mechanical properties of paper. In addition, non-wood fiber papers such as bamboo pulp paper have the problems of low strength and insufficient functionality, and traditional sizing processes are difficult to make up for these defects. Therefore, the existing technology cannot simultaneously solve multiple requirements such as antioxidant, antibacterial, moisture-proof and mechanical properties of paper, and there is also a lack of an efficient and environmentally friendly functional modified sizing agent. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing a tannic acid-based papermaking additive, which solves the problems in the prior art that neutral sizing agents have poor applicability under acidic conditions and that it is difficult to balance the antioxidant, antibacterial, hydrophobic and mechanical properties of paper.

[0005] To achieve the above objectives, the present invention is implemented by the following technical scheme: a method for preparing a tannic acid-based papermaking auxiliary agent, comprising the following steps: 1) Prepare tannic acid solution: dissolve tannic acid in deionized water and stir to form a uniform solution; 2) Prepare cationic starch solution: dissolve cationic starch in deionized water, heat and stir until a uniform solution is obtained; 3) preparing tannic acid-cationic starch emulsion: slowly dropping the cationic starch solution into the tannic acid solution, heating to a set temperature and maintaining the reaction, and cooling to obtain the tannic acid-cationic starch emulsion; 4) preparing a composite sizing solution: adding an alkyl ketene dimer emulsion to a tannic acid-cationic starch emulsion, stirring the mixture evenly, and obtaining a composite sizing solution; 5) The composite sizing solution is applied to the surface of bleached bamboo pulp paper, and coated paper is prepared by impregnation, pressing and drying.

[0006] Preferably, in step 1), the concentration of tannic acid is 1% to 6%, preferably 4%.

[0007] Preferably, in step 2), the concentration of cationic starch is 0.1% to 1%, preferably 0.4%.

[0008] Preferably, in step 3), the cationic starch solution is added to the tannic acid solution in a dropwise manner, and the dropwise addition speed is 2 ml / min to 10 ml / min, preferably 5 ml / min.

[0009] Preferably, in step 3), the gelatinization temperature is 80° C. to 100° C., preferably 95° C., and the reaction time is 20 minutes to 60 minutes, preferably 30 minutes.

[0010] Preferably, in step 4), the amount of alkyl ketene dimer added to the composite sizing solution is 0.1% to 1%, preferably 0.6%.

[0011] Preferably, in step 5), the immersion time of the sized paper is 10 seconds to 30 seconds, preferably 15 seconds; the pressing pressure is 0.3 MPa to 0.8 MPa, preferably 0.5 MPa; and the drying temperature is 90°C to 120°C, preferably 105°C.

[0012] Preferably, the composite sizing solution achieves the following technical effects through the antioxidant properties of tannic acid, the reinforcing properties of cationic starch and the hydrophobic properties of alkyl ketene dimer: The tensile index of paper is increased by more than 40%; The free radical scavenging rate reaches over 80%; The contact angle of the paper surface is increased to 120° to 135°.

[0013] Preferably, the preparation method is suitable for functional modification of bleached bamboo pulp paper, and the antibacterial properties of paper are improved by synergistic sizing, wherein the maximum inhibition zone diameter for Staphylococcus aureus reaches 35 mm to 40 mm.

[0014] Preferably, the application scope of the tannic acid-based papermaking additive includes but is not limited to food packaging paper, high-end cultural paper and special functional paper with antibacterial and antioxidant requirements.

[0015] The present invention provides a method for preparing a tannic acid-based papermaking auxiliary agent, which has the following beneficial effects: 1. The present invention successfully expands the application scope of the neutral sizing agent through the synergistic effect of tannic acid and cationic starch, so that it can still play a good sizing effect in the traditional acidic papermaking process. This feature breaks the situation where the application of neutral sizing agents is limited, and provides an innovative solution for the production of non-wood fiber paper such as bamboo pulp paper and straw pulp paper that need to maintain an acidic environment. At the same time, the expansion of the scope of application is conducive to the flexible adjustment of the papermaking process and improves the industrial adaptability of the sizing technology.

[0016] 2. By optimizing the ratio of tannic acid, cationic starch and AKD, the coated paper prepared by the present invention achieves significant improvements in multiple key performance indicators. The antioxidant performance of the coated paper is significantly enhanced, effectively preventing oxidative degradation; the hydrophobicity is significantly improved, greatly reducing the hygroscopicity of the paper; the mechanical properties are significantly optimized, ensuring the durability and damage resistance of the paper; the antibacterial performance is excellent, meeting the high requirements of food packaging and sanitary paper. These performance improvements make the coated paper more reliable and have high added value in practical applications.

[0017] 3. The preparation method of the present invention uses tannic acid and cationic starch from natural sources as main raw materials, supplemented by AKD as a hydrophobic agent, which completely replaces the synthetic chemicals used in the traditional sizing process. These natural raw materials are not only widely available and inexpensive, but also have good biodegradability, effectively reducing the potential pollution of the papermaking industry to the environment. At the same time, the preparation process of the present invention has low energy consumption and does not require additional chemical reagents, which meets the development requirements of green manufacturing and circular economy, and provides innovative ideas for the sustainable development of the papermaking industry.

[0018] 4. The composite sizing liquid proposed in the present invention can effectively make up for the deficiencies in its mechanical properties and functionality, and endow it with excellent antibacterial, antioxidant, moisture-proof and strength properties. Through these functional modifications, the performance of bamboo pulp paper has exceeded that of some straw pulp paper and wood pulp paper, further broadening its application scenarios in high-end food packaging paper, medical paper and special functional paper. This not only increases the added value of bamboo pulp paper, but also promotes the high-quality development of my country's bamboo pulp industry, and injects new vitality into the industrial upgrading of the papermaking industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0020] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Please see attached Figure 1 The present invention provides a method for preparing a tannic acid-based papermaking additive, describes in detail the composition of the additive formula, the preparation steps and the application in papermaking sizing, and verifies the effect of significantly improving the antioxidant, antibacterial, hydrophobic and mechanical properties of paper by combining the test analysis of physical and chemical properties. The following is the specific implementation content.

[0022] 1. Raw material ratio and characteristics 1.1 Tannic acid (TA) Properties: Polyphenol compounds extracted from natural plants, containing multiple phenolic hydroxyl groups (-OH) in the chemical structure.

[0023] Function: As the core antioxidant and antibacterial component, it enhances the stability of the sizing solution through electrostatic interaction with cationic starch, while giving the coated paper antioxidant and antibacterial properties.

[0024] Recommended dosage: mass concentration is 1% to 6%, preferably 4%.

[0025] 1.2 Cationic starch (CS) Properties: Modified starch, cationic groups introduced through etherification reaction , improving its bonding ability with paper fibers.

[0026] Function: It improves the stability of emulsion by combining with tannic acid and significantly improves the mechanical properties of paper through its reinforcing effect.

[0027] Recommended dosage: mass concentration is 0.1% to 1%, preferably 0.4%.

[0028] 1.3 Alkyl ketene dimer (AKD) Nature: Hydrophobic sizing agent, containing long-chain alkyl groups and reactive dimer structure .

[0029] Function: It combines with the hydroxyl (-OH) on the surface of paper fibers through esterification reaction to form a hydrophobic coating, which significantly improves the moisture-proof performance of paper.

[0030] Recommended dosage: mass concentration is 0.1% to 1%, preferably 0.6%.

[0031] 1.4 Deionized water Function: As a dissolving matrix, it provides a stable reaction medium for uniform dispersion and emulsification of raw materials.

[0032] 2. Preparation of tannic acid-cationic starch emulsion 2.1 Preparation of tannic acid solution Weigh 4 g of tannic acid and dissolve it in 50 ml of deionized water. Stir on a magnetic stirrer at 500 rpm for 10 minutes to ensure that the tannic acid is completely dissolved and a homogeneous and transparent solution is formed.

[0033] 2.2 Preparation of cationic starch solution Weigh cationic starch (e.g. 0.8 g) and dissolve it in 50 ml of deionized water. Mix at 50°C and 300 rpm until the solution is homogeneous.

[0034] 2.3 Gelatinization of tannic acid and cationic starch The cationic starch solution was added dropwise to the tannic acid solution at a rate of 5 ml / min while stirring at 300 rpm to prevent stratification.

[0035] The mixed solution was heated to 95°C and maintained for 30 minutes to allow the tannic acid and cationic starch to combine through electrostatic action to form a stable emulsion structure.

[0036] The emulsion was cooled to 60°C and set aside.

[0037] 2.4 Chemical bonding principle Electrostatic effect: The phenolic hydroxyl group in the tannic acid molecule is partially ionized into phenolic oxygen anions , the positively charged groups in cationic starch molecules It binds to it through electrostatic attraction to form a stable complex.

[0038]

[0039]

[0040] Hydrogen bonding: The unionized phenolic hydroxyl groups (-OH) in the tannic acid molecules form hydrogen bonds with water molecules, further enhancing the uniformity of the emulsion.

[0041] 3. Preparation of composite sizing solution 3.1 Add AKD 0.6 g of AKD emulsion was added to the prepared tannic acid-cationic starch emulsion, and the mixture was stirred at 60° C. for 10 minutes to uniformly disperse AKD in the emulsion.

[0042] 3.2 Emulsion stability The prepared composite sizing solution was sampled and placed in a glass container and left to stand for 24 hours to observe its stability. The results showed that the emulsion had no stratification or precipitation, proving that it had good stability.

[0043] 4. Preparation of coated sized paper 4.1 Preparation of base paper Pulp treatment: Take bleached bamboo pulp (320 g), soak it in 5 L of deionized water, and let it stand for 12 hours to soften the fibers.

[0044] Beating: Use a beater to process the bamboo pulp to 70°SR (Schober's beating degree) to prepare a uniform pulp.

[0045] Forming: Use a paper sheet former to make wet paper sheets with a diameter of 20 cm.

[0046] Drying: Use a press with a pressure of 0.5 MPa set, press for 5 min, and then dry in a plate dryer at 105 °C for 8 min.

[0047] 4.2 Coating and sizing Dipping: Immerse the wet paper completely in the composite sizing solution and keep the dipping time for 15 seconds.

[0048] Pressing: Place the impregnated paper in a press and press at a pressure of 0.5 MPa for 3 minutes to remove excess sizing liquid.

[0049] Drying: The paper was transferred to a drier at 105°C and dried for 15 minutes to obtain coated paper.

[0050] 5. Coated paper performance test 5.1 Antioxidant properties The antioxidant properties of coated paper were determined by DPPH free radical scavenging experiment. 50 mg of coated paper extract was reacted with DPPH solution, the absorbance was measured using a spectrophotometer, and the free radical scavenging rate was calculated:

[0051] The results showed that the free radical scavenging rate reached over 85%.

[0052] 5.2 Hydrophobicity The water contact angle of paper was measured using a contact angle tester. The results showed that the contact angle of the coated paper after sizing was 135°, significantly higher than the 0° of the unsizing paper.

[0053] 5.3 Mechanical properties Through tensile strength and tear length tests, the tensile index of sized paper increased by 42.5% and the tear length increased by 40.4%.

[0054] 5.4 Antimicrobial properties The antibacterial properties were determined by the inhibition zone test. The diameter of the inhibition zone of the coated paper against Staphylococcus aureus was 38 mm, and it also showed good antibacterial effect against Escherichia coli.

[0055] Example 1: Preparation of 4%TA-0.4%CS composite sizing solution Materials and proportions Tannic acid (TA): 4 g Cationic starch (CS): 0.4 g Alkyl ketene dimer (AKD): 0.6 g Deionized water: 100 ml Preparation steps Tannic acid solution: Add 4 g tannic acid into 50 ml deionized water and stir until completely dissolved.

[0056] Cationic starch solution: Dissolve 0.4 g of cationic starch in 50 ml of deionized water, heat to 50°C, and stir until uniform.

[0057] Gelatinization: cationic starch solution was added dropwise to tannic acid solution at a rate of 5 ml / min, heated to 95°C and maintained for 30 min, and cooled to 60°C.

[0058] Composite sizing solution: Add 0.6 g AKD to the emulsion, stir evenly, and let it stand for 24 hours to stabilize.

[0059] Gluing process Dipping time: 15 seconds Pressing pressure: 0.5 MPa, time: 3 minutes Drying temperature: 105°C, time: 15 minutes Example 2: Preparation of 6%TA-0.6%CS composite sizing solution Materials and proportions Tannic acid (TA): 6 g Cationic starch (CS): 0.6 g Alkyl ketene dimer (AKD): 0.6 g Deionized water: 100 ml Preparation steps Tannic acid solution: Add 6 g tannic acid into 50 ml deionized water and stir until completely dissolved.

[0060] Cationic starch solution: Dissolve 0.6 g of cationic starch in 50 ml of deionized water, heat to 50°C, and stir until uniform.

[0061] Gelatinization: cationic starch solution was added dropwise to tannic acid solution at a rate of 5 ml / min, heated to 95°C and maintained for 40 min, and cooled to 60°C.

[0062] Composite sizing solution: Add 0.6 g AKD to the emulsion, stir evenly, and let it stand for 24 hours to stabilize.

[0063] Gluing process Dipping time: 15 seconds Pressing pressure: 0.5 MPa, time: 3 minutes Drying temperature: 105°C, time: 15 minutes Comparative Example 1: No Tannic Acid (CS and AKD Only) Materials and proportions Cationic starch (CS): 0.4 g Alkyl ketene dimer (AKD): 0.6 g Deionized water: 100 ml Preparation steps Cationic starch solution: Dissolve 0.4 g of cationic starch in 50 ml of deionized water, heat to 50°C, and stir until uniform.

[0064] Gelatinization: Heat to 95°C, hold for 30 minutes, and cool to 60°C.

[0065] Composite sizing solution: Add 0.6 g AKD to the emulsion, stir evenly, and let it stand for 24 hours to stabilize.

[0066] Gluing process Dipping time: 15 seconds Pressing pressure: 0.5 MPa, time: 3 minutes Drying temperature: 105°C, time: 15 minutes Comparative Example 2: No AKD (only TA and CS) Materials and proportions Tannic acid (TA): 4 g Cationic starch (CS): 0.4 g Deionized water: 100 ml Preparation steps Tannic acid solution: Add 4 g tannic acid into 50 ml deionized water and stir until completely dissolved.

[0067] Cationic starch solution: Dissolve 0.4 g of cationic starch in 50 ml of deionized water, heat to 50°C, and stir until uniform.

[0068] Gelatinization: Add the cationic starch solution to the tannic acid solution at a rate of 5 ml / min, heat to 95°C, maintain for 30 minutes, and cool to 60°C.

[0069] Gluing process Dipping time: 15 seconds Pressing pressure: 0.5 MPa, time: 3 minutes Drying temperature: 105°C, time: 15 minutes Comparative Experimental Design and Data Table Experimental design In order to verify the influence of different sizing solution formulas on paper performance, the following indicators were tested: Antioxidant performance: Passed the DPPH free radical scavenging rate test.

[0070] Hydrophobicity: Test water contact angle.

[0071] Mechanical properties: tensile index and breaking length.

[0072] Antibacterial properties: The antibacterial properties were evaluated by the diameter of the inhibition zone.

[0073] Experimental results: Experimental Group DPPH free radical scavenging rate (%) Water contact angle (°) Tensile index (N·m / g) Fracture length (km) Diameter of inhibition zone (mm) Example 1 85 135 57 5.9 38 Example 2 88 128 55 5.7 36 Comparative Example 1 0 136 45 4.5 0 Comparative Example 2 70 0 49 5.1 32 According to the data, the free radical scavenging rates of Example 1 and Example 2 are significantly higher than those of Comparative Example 1 and Example 2, verifying the significant antioxidant effect of tannic acid. The water contact angles of Example 1 and Example 2 are significantly higher than those of Comparative Example 2, indicating the contribution of AKD to the hydrophobicity. The tensile index and breaking length of Example 1 and Example 2 are significantly better than those of the Comparative Example, indicating that the synergistic effect of tannic acid and cationic starch improves the mechanical properties of paper. The antibacterial effect of Example 1 and Example 2 on Staphylococcus aureus is significantly better than that of the Comparative Example, indicating that tannic acid imparts excellent antibacterial properties to the coated paper.

[0074] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a tannic acid-based papermaking auxiliary agent, characterized in that: The following steps are involved: 1) Prepare tannic acid solution: dissolve tannic acid in deionized water and stir to form a uniform solution; 2) Prepare cationic starch solution: dissolve cationic starch in deionized water, heat and stir until a uniform solution is obtained; 3) preparing tannic acid-cationic starch emulsion: slowly dropping the cationic starch solution into the tannic acid solution, heating to a set temperature and maintaining the reaction, and cooling to obtain the tannic acid-cationic starch emulsion; 4) preparing a composite sizing solution: adding an alkyl ketene dimer emulsion to a tannic acid-cationic starch emulsion, stirring the mixture evenly, and obtaining a composite sizing solution; 5) The composite sizing solution is applied to the surface of bleached bamboo pulp paper, and coated paper is prepared by impregnation, pressing and drying.

2. The method for preparing a tannic acid-based papermaking aid according to claim 1, characterized in that: In the step 1), the concentration of tannic acid is 1% to 6%, preferably 4%.

3. The method for preparing a tannic acid-based papermaking aid according to claim 1, characterized in that: In the step 2), the concentration of cationic starch is 0.1% to 1%, preferably 0.4%.

4. The method for preparing a tannic acid-based papermaking aid according to claim 1, characterized in that: In the step 3), the cationic starch solution is added dropwise to the tannic acid solution at a dropping speed of 2 ml / min to 10 ml / min, preferably 5 ml / min.

5. The method for preparing a tannic acid-based papermaking aid according to claim 1, characterized in that: In the step 3), the gelatinization temperature is 80° C. to 100° C., preferably 95° C., and the reaction time is 20 minutes to 60 minutes, preferably 30 minutes.

6. The method for preparing a tannic acid-based papermaking aid according to claim 1, characterized in that: In the step 4), the amount of alkyl ketene dimer added to the composite sizing solution is 0.1% to 1%, preferably 0.6%.

7. The method for preparing a tannic acid-based papermaking aid according to claim 1, characterized in that: In the step 5), the immersion time of the sized paper is 10 seconds to 30 seconds, preferably 15 seconds; the pressing pressure is 0.3 MPa to 0.8 MPa, preferably 0.5 MPa; and the drying temperature is 90° C. to 120° C., preferably 105° C.

8. The method for preparing a tannic acid-based papermaking aid according to claim 1, characterized in that: The composite sizing solution achieves the following technical effects through the antioxidant properties of tannic acid, the reinforcing properties of cationic starch and the hydrophobic properties of alkyl ketene dimer: The tensile index of paper is increased by more than 40%; The free radical scavenging rate reaches over 80%; The contact angle of the paper surface is increased to 120° to 135°.

9. The method for preparing a tannic acid-based papermaking aid according to claim 1, characterized in that: The preparation method is suitable for functional modification of bleached bamboo pulp paper, and the antibacterial properties of the paper are improved by synergistic sizing, wherein the maximum inhibition zone diameter for Staphylococcus aureus reaches 35 mm to 40 mm.

10. The method for preparing a tannic acid-based papermaking auxiliary agent according to claim 1, characterized in that: The application scope of the tannic acid-based papermaking additive includes but is not limited to food packaging paper, high-end cultural paper and special functional paper with antibacterial and antioxidant requirements.